Blended Learning Method in Enhancing Students' Critical Thinking Skills: Challenges and Opportunities - Abdul Haris Sunubi; Bachtiar Bachtiar (AL-ISHLAH: Jurnal Pendidikan, 2022)
The aim of this study is to determine the challenges and opportunities of the blended learning method in improving students' critical thinking skills at Junior High Schools in South Sulawesi. This type of research is a case study research with a qualitative approach. This research was conducted in 2022 at Senior High School in South Sulawesi in English subjects with two principals, 2 English teachers, and 45 students as respondents. Data collection techniques using observation to see the condition of this school, both the facilities and the infrastructure, interviews for students and teachers to get information and data about blended learning, and documentation is students' scores from some subjects. The result of this study is the blended learning method can improve students' critical thinking skills. The conclusion is that teachers must be able to develop innovative and creative teaching materials.